Online learning environments for the promotion of undergraduate research in pandemic times: A case study in an engineering program - Cáceres Montero, Ludy Margarita (2023)
This case study explores the use of online learning environments as an alternative tool for the promotion of undergraduate research culture within an engineering program during the COVID-19 pandemic times. This context entailed the transition from face-to-face to online learning environments, which was taken as an opportunity for the diffusion and socialization of outstanding research projects developed by undergraduate students within the classroom, through the launching of an online event and a virtual permanent exhibition. The results of this case study were measured through quantitative indicators related to the number of research projects submitted by the students for participating in this exhibition, the number of courses participating through these projects, and the number of professors involved. Participation of students and professors increased by 85% and 90%, respectively, comparing the online environment to the previous face-to-face one. Consequently, it was concluded that the use of online learning environments supports the promotion of undergraduate research culture, by increasing the interest of students for the socialization of their research results.